Analysis Of Fundamental Factors In Planning And Teaching Conversation (keith s. Folse overview) - Khudriyah (Jurnal Pendidikan Islam, 2019)
bstract: Conversation is part of speaking skill. Speaking is one of the English skill that must be taught since Junior High School. Teaching conversation needs hard work, the teachers should know everything related to the teaching. There are many factors influnce the teaching of conversation. According to Folse the one who has taught ESL / EFL for more than thirty five years in some countries. He has written many books on vocabulary, reading, speaking, writing, grammar, and listening, including the popular Great Wr iting series or Heinle Cengage. He has won many teaching and research awards said that there are five fundamental factors in planning and teaching conversation class such as learner’s age, profeciency, level, and goal; the school curriculum; the topic bein g discussed; the two language in the task and for the task, and the activity serves as vehical for conversation.